AUDIT JUDGMENT: PENGALAMAN AUDITOR, SKEPTISISME AUDITOR DAN LOCUS OF CONTROL - Yanto, Desri; Fithri, Eka Jumarni; Oktarini, Kurnia Widya; Anggraini, Fadiyah Lefi; Athaillah, M. Faishal Akbar; Utami, Adelia Rizky (Jurnal Riset Terapan Akuntansi, 2026)
This study aims to empirically examine and analyze the effect of Auditor Experience, Auditor Skepticism, and Locus of Control on Audit Judgment quality. This study employs a quantitative approach. Data were collected through the distribution of questionnaires to auditor respondents working at the Audit Board of the Republic of Indonesia (BPK RI) Representative of South Sumatra. The data analysis technique employed was the Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS) using SmartPLS 3.0 software. Based on the hypothesis testing results, it was found that Auditor Skepticism and Locus of Control have a positive and significant effect on Audit Judgment. This indicates that the higher the level of professional skepticism and the stronger the internal locus of control of an auditor, the better the resulting audit judgment. Conversely, the results showed that Auditor Experience does not have a significant effect on Audit Judgment, indicating that the length of work tenure does not necessarily guarantee accuracy in audit decision-making. Keywords: : Audit Judgment, Skepticism, LOC, SmartPLS.